Factor X Levels, Polymorphisms in the Promoter Region of Factor X, and the Risk of Venous Thrombosis - de Visser, Marieke C. H.; Poort, Swibertus R.; Vos, Hans L.; Rosendaal, Frits R.; Bertina, Rogier M. (Thrombosis and Haemostasis, 2001)
Elevated levels of procoagulant proteins factor II, factor VIII, factor IX, factor XI and fibrinogen are associated with an increased risk of venous thrombosis. In a population-based case-control study on venous thrombosis (Leiden Thrombophilia Study, LETS) we investigated whether elevated coagulation factor X (FX) levels are a risk factor for venous thrombosis and whether FX levels are determined by polymorphisms in the promoter region of the FX gene. We found that subjects with high FX levels (above the 90th percentile, ≥ 126 U/dl) had a 1.6-fold increased risk of venous thrombosis. The highest risk (OR = 4.3, 95% confidence interval: 1.5-12) was found in the subgroup of premenopausal women who are not using oral contraceptives. However, these estimated risks disappeared after adjustment for other vitamin K-dependent coagulation factors II, VII and IX. To study the influence of genotypic variation on plasma FX levels we assessed four polymorphisms in the promoter region of the FX gene: a TTGTGA insertion between position -343A and -342G, a C/T polymorphism at position -222, a C/A polymorphism at position -220 and a C/T polymorphism at position -40. No relationship between these investigated genotypes and FX levels was observed. We conclude that high FX levels predict risk of thrombosis, but are not a risk factor for venous thrombosis when the levels of other vitamin K-dependent proteins are taken into account.
Keywords: Factor X; venous thrombosis; polymorphisms